Strain-rate Dependence of Compressive Strength in a Granitic Rock - R. Ranjan (International Society of Explosives Engineers, 2010)
Stanstead granite has been investigated with respect to its dynamic compressive strength and its strain-rate dependency. A standard Split-Hopkinson Pressure Bar (SHPB) apparatus has been employed to generate strain rates of up to ~500/s through high-velocity impact. The diameters of the test samples were 19 mm, and tested under impact velocities up to ~20m/s. It is found that even within this limited range of strain rates, the dynamic compressive strength for the granite showed nearly a 100% increase in value compared to those obtained under static loading conditions (e.g. compressive strength of 394 MPa at a strain-rate of 600/s, compared to 215 MPa obtained under static loading). The details of the test are described in terms of incident, reflected and transmitted stress pulses, along with means to achieve stress equilibrium in the test samples under dynamic loading conditions. The advantage and drawback of the use of ‘pulse shaping’ techniques to achieve dynamic stress equilibrium are also detailed.